Parámetros de forma de una cuenca referenciados con el círculo y la lemniscata, aplicados a la subcuenca del río Llanganuco – Perú. (Aporte Santiaguino, 2023)
The objective of the research consisted of deducing the shape parameters of a basin referenced with the lemniscate, then carrying out a comparative analysis with the shape parameters referenced with the circle and applying them to the sub-basin of the Llanganuco river.The procedure followed, deduction of the area and perimeter of the lemniscate, deduction of the shape parameters of a basin referenced with the lemniscate, comparison of the shape parameters referenced with the circle and the lemniscate. Besides, the shape parameters referenced with the circle and the lemniscate of the Llanganuco river sub-basin were determined.The ratio of the compactness coefficient of a basin referenced with the circle and the lemniscate is 1,048; the ratio of the ratio of circularity and the lemniscate of a basin is 0,914 and the ratio of the ratio of elongation of a basin referenced with the circle and with the lemniscate is 0,798. For the Llanganuco river sub-basin, the compactness coefficient referenced to the lemniscate is 1,420; the lemniscate ratio is 0,495; the lemniscate referenced elongation ratio is 0,687 and the Chorley lemniscate ratio is 0,856.Keywords: basin; parameter; lemniscate; elongation.